Understanding and management of anti-N-methyl-D-aspartate receptor encephalitis from a child psychiatry perspective: report of five cases. Issue 2 (4th March 2022) - Dogan, Nurhak; Subasi, Hilal; Erbasan, Zeynep Irem; Tahillioglu, Akin; Kanmaz, Seda; Kose, Sezen; Ozbaran, Burcu; Serin, Hepsen Mine
ABSTRACT: Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is a rare autoimmune entity in psychiatry literature that occurs when antibodies attack NMDA-type glutamate receptors in the brain. Principle clinical features include a neurological domain such as seizure, orofacial dyskinesia, dystonia, and choreic-like movements of extremities. Also the psychiatric manifestations of this form of encephalitis may vary from psychotic-like symptoms to mood symptoms like depression or mania. Herein we report on five female child cases diagnosed with anti-NMDAR encephalitis, presented with both neurological and psychiatric clinical picture, and highlight the trajectory of disorder from a psychiatric perspective.